QUIZ APP - Atchaya.K, Elakkiya.S (International Journal of Modern Agriculture, 2021)
The main objective of the project on QUIZ APP deals with the enriching knowledge of the user. This deals with the development of android-based multiple-choice question examination system. It gives questions for the selected categories. This project is developed as an android application using Android SDK 2.2 as front end. Since mobile network is available at maximum areas so this app can be used for the knowledge testing of any person specially candidates of software company who needs a specific skill for job. Development of android-based Quiz application is mainly required for students and learners to prepare themselves for different examinations directly through smart phones and tablets in hands. It is very effective and user friendly. This deal with the development of android-based multiple-choice question examination system. The main goal of the application is to enable users to practice for subjective test.